Radiation and Chemotherapy are Associated with Altered Aortic Aneurysm Growth in Patients with Cancer: Impact of Synchronous Cancer and Aortic Aneurysm. (August 2022) - Becker von Rose, Aaron; Kobus, Kathrin; Bohmann, Bianca; Lindquist-Lilljequist, Moritz; Eilenberg, Wolf; Bassermann, Florian; Reeps, Christian; Eckstein, Hans-Henning; Trenner, Matthias; Maegdefessel, Lars; Neumayer, Christoph; Brostjan, Christine; et al.
Abstract : Objective: The purpose of this study was to assess the associations between malignancy, therapeutic regimens, and aorto-iliac aneurysm (i.e., abdominal aortic aneurysm [AAA]) growth rates. Methods: A retrospective single centre analysis identified patients with an AAA plus cancer. Patients who had two or more computed tomography angiograms over six months or more and additional malignancy were included. Clinical data and aneurysm diameters were analysed. AAA growth under cancer therapy (chemotherapy or radiation) was compared with a non-cancer AAA control cohort and to meta-analysis data. Statistics included t tests and a linear regression model with correction for initial aortic diameter and type of treatment. Results: From 2003 to 2020, 217 patients (median age 70 years; 92% male) with 246 aneurysms (58.8% AAA) and 238 malignancies were identified. Prostate (26.7%) and lung (15.7%) cancer were most frequently seen. One hundred and fifty-seven patients (72.3%) received chemotherapy, 105 patients (48.4%) radiation, and 79 (36.4%) both. Annual AAA growth (mean ± standard deviation) was not statistically significantly different for cancer and non-cancer patients (2.0 ± 2.3 vs. 2.8 ± 2.1 mm/year; p  = .20). However, subgroup analyses revealed that radiation was associated with a statistically significantly reduced mean aneurysm growth rate compared with cancer patients without radiation (1.1 ± 1.3 vs. 1.6 ± 2.1 mm/year; p  = .046) and to the non-cancer control cohort (1.7 ± 1.9 vs. 2.8 ± 2.1 mm/year; p  = .007). Administration of antimetabolites resulted in statistically significantly increased AAA growth (+ 0.9 mm/year; p  = .011), while topoisomerase inhibitors (– 0.8 mm/year; p  = .17) and anti-androgens (– 0.5 mm/year; p  = .27) showed a possible trend for reduced growth. Similar observations were noted for iliac aneurysms ( n  = 85). Additionally, the effects persisted for chemotherapy combinations (2.6 ± 1.4 substances/patient). Conclusion: Patients with cancer and concomitant aortic aneurysms may require intensified monitoring when undergoing specific therapies, such as antimetabolite treatment, as they may experience an increased aneurysm growth rate. Radiation may be associated with reduced aneurysm growth.